Curcumin- and Piperine-Loaded Emulsomes as Combinational Treatment Approach Enhance the Anticancer Activity of Curcumin on HCT116 Colorectal Cancer Model - Bolat, Zeynep Busra; Islek, Zeynep; Demir, Bilun Nas; Yilmaz, Elif Nur; Sahin, Fikrettin; Ucisik, Mehmet Hikmet (Frontiers in Bioengineering and Biotechnology, 2020)
Combination chemotherapy, administrating two chemotherapeutic agents concurrently, comes into prominence, as the heterogeneity or the level of the disease necessitates a collaborative action. Curcumin, isolated from turmeric, and piperine, isolated from black long pepper, are two dietary polyphenols studied for their intrinsic anti-cancer properties, against various cancer types including colorectal cancer (CRC). Furthermore, piperine synergistically improves the therapeutic effect of curcumin. Addressing this synergistic behavior, this study combines curcumin and piperine within emulsome nanoformulations. Curcumin- (CurcuEmulsomes) and piperine-loaded emulsomes (PiperineEmulsomes) have established a uniform, stable, spherical dispersion with average diameters of 184.21 and 248.76 nm, respectively. The solid tripalmitin inner core achieved encapsulation capacities of up to 0.10 mg/ml curcumin and 0.09 mg/ml piperine content. While piperine treatment alone – in its both free and emulsome forms – showed no inhibition in the proliferation of HCT116 cells in vitro, its presence as the second drug agent besides curcumin synergistically enhanced curcumin’s effect. Combination of 7 µM PiperineEmulsome and 25 µM CurcuEmulsome concentrations was found to be most effective with an inhibition of cell proliferation of about 50% viability. Cell cycle arrest at G2/M phase and induced apoptosis verified the improved anti-cancer characteristics of the therapy. While CurcuEmulsomes achieved a 4-fold increase in Caspase 3 level, combination of treatment with PiperineEulsomes achieved a 6-fold increase in the level of this apoptotic marker. Improving the bioavailabilities of curcumin and piperine meant CurcuEmulsome and PiperineEmulsome formulations were achieved. Combinational treatment of HCT116 cells with CurcuEmulsomes and PiperineEmulsomes synergistically improved the anticancer activity of the compounds and highlighted the potential of the approach for further in vivo studies.